Wearable devices for health remote monitor system - Caixeiro, Tiago José Pardal (2022)
It is feasible to see how communication and information technology have advanced at a rapid pace in today’s world. The introduction and emergence of wearable technology is one aspect that contributes to this advancement and has the potential to be an innovative solution to healthcare challenges, since it may be used for illness prevention and maintenance, such as physical monitoring, as well as patient management. To address some of the healthcare challenges, this research thesis provides a research methodology, research questions, and hypotheses for constructing an health remote monitoring system with alerts and continuous monitoring employing wearable devices capable of collecting biometric data on human health. The concept was then proven by the development of a prototype using wearable devices connected to a microcontroller, which transmits its data via MQTT Protocol to a Node-RED powered dashboard that handles health metrics monitoring and where all monitoring performed, and alarms generated can be viewed in real-time. All this data is delivered to a MongoDB database for further analysis and visualization. To demonstrate the effectiveness and capabilities of this prototype, it was used in the real world and the results were acquired from two distinct users. The results were very favorable and conclusive, demonstrating that the created prototype was satisfactory in providing data to support the developed hypotheses and research questions.